Success Factors of CIMB Group's Financial Performance (2005-2011) - Rosilawati, Mahamad Jusob (2012)
This study has focused on the success factors on bank performance and profitability determinants. Bank profitability is expected to be receptive to macroeconomic control variables. CIMB Group has been selected to this research because of within 2005 until 2011 CIMB Group becomes stronger as major player and 2nd largest financial services provider by assets in a banking sector in Malaysia. Even though after Sub Prime crisis on 2008, CIMB Group still can maintain and expand the business out of Malaysia. The main objective of this study to identify success factors of CIMB Group performance based on their financial report over a 7 years period from 2005 until 2011. This study identifies determinants of CIMB Group success comprising of CIMB Bank Berhad, CIMB Islamic and CIMB Investment Bank performance. The study utilized the secondary data obtained primarily from the CIMB Annual Report and Audited Financial Report. This study chosen trend analysis, descriptive analysis, correlation analysis, multiple regression and regression coefficient analysis to identify the determinant of CIMB Group success factor comprising of CIMB Bank, CIMB Islamic and CIMB Investment. Thirteen variables used to complete this study. Return on Asset (ROA) is Dependent Variable. Independent Variables are Net Interest Margin, Asset Quality, Loan Deposit, Size, Capital Adequacy, Leverage, Market Capitalization Change, Loan Portfolio based on type of customer (individual) and Loan Portfolio (variable rate) Gross Domestic Product, Base Lending Rate and Inflation.